Respiratory Drugs Dispensed Without Prescription in Dhaka City: Respiratory drugs dispensed without prescription - Sultana, Nusrat; Parvin, Roksana; Ahmad, Rahnuma; Shamsuddoha, Nazla; Naoreen, Rifat; Jahan, Mahmuda (Journal of the Medical College for Women & Hospital, 2024)
Background: Self-medication is a trend that may cause more damage than good. In low-middle income countries like Bangladesh it is quite easy to obtain medicine without prescription which may lead to several adverse effects or over medication. This scenario of our country needs to be fully assessed. Aim: To survey the age group of patients, number of drugs sold and cost of the drug for patients in different respiratory categories of drug used in Uttara in Dhaka City. Materials and Method: Cross-sectional survey records of 30 questionnaires from 3 big medicine shops for 10 selling time random record for patients from each six (6) categories of age group, dispensed medicine between January 2017 to June 2017 was reviewed. Results: The study observed the mean (±SD) of quantity of respiratory drug (inhaler) purchased without prescription was higest among the age groups of 10-18 years and 42-55 years (0.77±0.43 and 0.67 ± 0.55 respectively) which was statistically significant (p<0.01). The mean±SD of the money spent to make inhaler purchase was significantly high in all age groups, in particular among individuals in the age groups of 42-55 years (166.67±136.69) which was statistically significant p<0.01. The quantity of antihistamine purchased and the amount spent for its purchase in different age groups revealed the higest quantity was purchased by the age group of 25-32 years and the higest amount spent to make antihistamine purchase was by those in age group of 42-55 years (3.04±0.74 and 29.85±20.89 respectiely) which were statistically significant (p<0.01). J Med Coll Women Hosp. 2024; 20(2): 30-36